Participation in GVCs and the size of an economy – the case of developed and developing economies - Fronczek, Małgorzata (Udział w GVC a wielkość gospodarki – przypadek krajów rozwiniętych i rozwijających się, 2020)
The article aims to examine the relationship between the participation of developed and developing countries in GVCs and the size of their economies (GDP was adopted as a measure of the size of an economy). The results indicated a moderate but negative relationship between the GVC index and the GDP value, which means that larger countries were less involved in GVCs. However, the separation of developed countries from developing countries for the purpose of the analysis yielded interesting results. The calculations showed that the participation of developing countries in GVCs was on average only slightly weaker than the involvement of developed countries, but the relationship between the examined variables was only true for developed countries (the correlation coefficient indicated a moderate negative relationship). The participation of developing countries in GVCs, on the other hand, was not related to the size of their economies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 42-51
Keywords: trade in value added; globalization; international trade; global value chains; GVC; handel według wartości dodanej; globalizacja; handel międzynarodowy